LEARNING ISSUES JUMP SITTING BY THE HANDS SALT 1Â½ GYMNASTS OF AGES 10 TO 11 YEARS - Gabriela, Constantin (Arena-Journal of Physical Activities, 2013)
Artistic gymnastics, an old discipline, has recently developed, especially nowadays. Its evolution in the last four years was rapid, being characterized by a refined technique, which implies virtuosity and by very risky elements. Among other sports, gymnastics has a very well defined status, even it is in a continuous process of renewal and modernization. It can be seen in daily practice, in different ways, depending on teachers and gymnasts.